RETRACTED: The Impact of Underwater Sound on Aquatic Animals – And Especially Fishes - Donald Hawkins, Anthony (International Marine Science Journal, 2022)
This article has been retracted on 30 May 2023. VIEW THE RETRACTION NOTICE (https://doi.org/10.14302/issn.2643-0282.imsj-25-5851) Underwater sounds from human sources can have detrimental effects upon aquatic animals, including fishes, and currently such sounds are very common. It is important to examine such anthropogenic sounds and their effects upon aquatic animals, so that it is possible to introduce protective regulations. Fishes and other aquatic animals can detect underwater sounds and use them to obtain key information about the environment around them. Sounds travel rapidly over great distances in water and can provide detailed information on the presence of prey, predators, and related fishes, while the overall acoustic scene provides the fishes with key information about their environment. Although some of the background noise is generated by natural sources, including the precipitation of rain and snow, and wind and waves, many underwater sounds now come from anthropogenic sources, often termed “noise”. Some of these human-made sounds can kill or injure fishes and other aquatic animals, also impairing their hearing, and altering their behavior. There is a need for more work on the impact of human-made underwater noise upon the fitness of aquatic animals. This paper considers the gaps in information that must be resolved. The effects that need to be considered include death and injuries, physiological effects, and changes in behavior.
Keywords: aquatic animals; Underwater sounds; wind and waves; environment; rain and snow